Workload, work stress, and internal communication as predictors of employee loyalty in a regional agriculture office - Nurhaqiqi Rizqi; Surya Bakti (Priviet Social Sciences Journal, 2026)
This study examined workload, work stress, and internal communication as predictors of employee loyalty among civil servants or Aparatur Sipil Negara (ASN) at the Asahan Regency Agriculture Office in North Sumatra, Indonesia. Drawing on the Job Demands-Resources (JD-R) model and Social Exchange Theory, this study uses a quantitative explanatory design with saturation sampling of the fully eligible workforce (N = 31). Data were collected using a five-point Likert questionnaire and analyzed using multiple linear regression. The results show that workload is positively associated with employee loyalty (B = 0.508, p = .007), and internal communication is also positively associated (B = 0.389, p = .025), while work stress is not statistically significant (B = -0.050, p = .618). The three predictors were jointly significant (F(3, 27) = 52.71, p < .001; adjusted R² = .838), although the high explanatory power should be interpreted cautiously, given the small, single-site, self-report design. This study contributes to public-sector HRM by showing that, in a tenure-protected regional agriculture office, a manageable workload and effective communication may be more closely linked to loyalty than work stress. The findings are context-specific and should be tested in larger, multi-agency studies.